Treatment of Graves’ disease in Brazil: results of a survey among endocrinologists - Villagelin, Danilo; Mazeto, Glaucia M. F. S. [UNESP]; Junior, Cléo Otaviano Mesa; Ramos, Helton Estrela; Scheffel, Rafael Selbach; Chiamolera, Maria Izabel; Perini, Nicolas; Ronconi, Thiago Luis; Texeira, Patricia (Archives of Endocrinology and Metabolism, 2023)
Objective: The objective of the study was to determine how physicians in Brazil manage Graves’ disease in different scenarios including extrathyroidal manifestations. Materials and methods: This study was conducted via a digital survey. The respondents (n = 573) answered multiple-choice questions based on a clinical case and variations of the case regarding laboratory and imaging evaluation, treatment choice, and follow-up. Results: The preferred initial treatment chosen by 95% of the respondents was ATD with a preferred treatment duration of 18-24 months. For 5% of the respondents, RAI was the initial treatment of choice. None of the respondents chose thyroidectomy. When presented with a patient with a desire for pregnancy in the near future, most respondents (69%) opted for ATD as the initial treatment. For a patient with signs of mild to moderate Graves’ orbitopathy, ATD remained the initial therapy for 93.9% of the respondents. For patients initially treated with ATD with disease recurrence after ATD interruption, most respondents (60%) chose definitive treatment with RAI. A similar survey published in 2011 by Burch and cols. had results comparable to those of the present survey but with a higher proportion of respondents choosing RAI (45% in the 2011 survey versus 5% in the present survey). Conclusion: Brazilian endocrinologists choose ATD as the initial management of Graves’ disease, and most choose RAI as a definitive treatment for a patient with relapse after ATD therapy.
Keywords: Graves' disease; hyperthyroidism treatment; Treatment